Penggunaan Platform Padlet sebagai Media Pembelajaran Daring pada Perkuliahan Teknologi Pendidikan Islam di Masa Pandemi Covid-19 - Alghozi, Alan Alifudin; Salsabila, Unik Hanifah; Sari, Sinta Ratna; Astuti, Ramadhani Tri; Sulistyowati, Hassasah (ANWARUL, 2021)
This resarch emphasizes that the use of the padlet platform as an online learning medium during the COVID-19 pandemic in educational technology courses has a positive impact on increasing student activity and skills in ongoing teaching and learning activities, especially in the current learning conditions that use the online system. Education is carried out online using the Padlet platform, where students feel happy using the Padlet platform because it has complete and attractive features, Padlet allows lecturers and students to carry out teaching and learning activities simultaneously or which is flexible, which is easily accessible anywhere and anytime. The method used is a qualitative method by conducting a survey on the padlet application by distributing the G-form as research analysis data to UAD students to find out their perception of the use of padlets as online learning media in the COVID-19 pandemic era.